2013
DOI: 10.15376/biores.8.4.4899-4911
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Saccharification and L-lactic Acid Fermentation of Corn Stover Pretreated with Liquid Hot Water by Rhizopus oryzae

Abstract: aCorn stover was pretreated with liquid hot water (LHW) to enhance its enzymatic hydrolysis and L-lactic fermentation. The cellulose conversion rate and L-lactic acid concentration were used to evaluate LHW pretreatment performance. Results showed that the optimum conditions for the LHW pretreatment of corn stover are a reaction temperature of 190 °C for 20 min and a solid-to-liquid ratio of 1:10. The cellulase loading was 30 filter paper units per gram of oven-dried, water-insoluble solid. These conditions re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…LHW is a form of pretreatment that does not use any catalysts or chemicals (Kou et al 2013). During LHW pretreatment, water and acetyl groups within hemicelluloses, which act as acids at elevated temperatures (generally at 160 to 240 o C), can catalyze hydrolysis of hemicelluloses to hemicellulose oligomers and hemicellulose monomers (Cara et al 2007;Wan and Li 2011;Xiao et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…LHW is a form of pretreatment that does not use any catalysts or chemicals (Kou et al 2013). During LHW pretreatment, water and acetyl groups within hemicelluloses, which act as acids at elevated temperatures (generally at 160 to 240 o C), can catalyze hydrolysis of hemicelluloses to hemicellulose oligomers and hemicellulose monomers (Cara et al 2007;Wan and Li 2011;Xiao et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, plant straw fiber [21,22], kitchen waste [24], and paper sludge [17,19,20] can also be used as substrates. In addition, previous studies have reported on the use of agriculture wastes, such as cotton cellulose [4], corn stover [2,14], and wheat straw [5,16], for lactic acid production.…”
Section: Introductionmentioning
confidence: 99%
“…Pretreatment is essential to achieving high-efficiency conversion of bioethanol with lignocellulosic biomass. Among the different types of pretreatment, liquid hot water (LHW) pretreatment has been demonstrated to be an effective method for several lignocellulosic biomass types (Kou et al 2013;. After LHW pretreatment, the lignocellulosic biomass is divided into prehydrolysates that contain a large number of fivecarbon sugars and water-insoluble solids (WIS), which mainly consist of glucan and lignin.…”
Section: Introductionmentioning
confidence: 99%